Monaghan, Terry (London, 2013)
2013 "Monaghan, Terry", 2013, HistoryTalk Terry was born in 1943 and grew up in Paddington, west London. He went to Queens Park and Marylebone grammar schools. From his schooldays he was a radical and was involved in the music scene in the 1960s. his parents were both teachers and in the CPGB. He attended Regent Street Polytechnic but then went to work on building sites and factories, for example the Walls meat factory and CAV as an inspector in the 1960s and AEC and later Heathrow Airport . He describes working conditions, the shop- floor regime and production process. He notes the engineering sector in west London- the era of mass factories and its destruction as well as the historical process from WW2. He also notes the Irish migration to west London and the blacklists of militants as well as Caribbean immigration to work on London Transport. He returned to HE in the 1970s at the City of London Poly and then got a job there as AVA technician for 15 years. He was also closely involved with dance. He discusses how working class people organise themselves at all levels.